The adoptions of human resource management functions in small and medium enterprise : case study at Pengkalan Chepa 2 industrial zone / Nik Nawwar Tasnim Nik Abdul Rahman - Nik Abdul Rahman, Nik Nawwar Tasnim (2012)
The focus of this study is to investigate the adoptions of human resource management functions in small and medium enterprise, where the case study is at Pengkalan Chepa 2 Industrial Zone. The objective of this study is to determine the adoptions of human resource management functions in small and medium enterprise. The second objective of this study is to know the relationship between the adoptions of human resource management functions in small and medium enterprise and training and development, performance appraisal, and compensation and reward. The variables involve in this research study are the adoptions of human resource management functions in small and medium enterprise as the dependent variable, while the independent variables are training and development, performance appraisal, and compensation and reward. The descriptive research design is being use in this research study. The sampling frames of this research study are the factory workers who work for Falasino Sdn Bhd, Terang Nusa Sdn Bhd, Rohm-Wako Electronic (M) Sdn Bhd, and Era Bayam Kota Sdn Bhd. From this research, the result shows that none of human resource management functions is being adopted by the company